Estatuto jurídico del concebido - Zappalá, Francesco (2023)
The main issue with regard to the legal protection of fetuses is determining when life is understood to begin or exist. Common law and civil law systems have different statutory, case law, and doctrinal approaches to this problem. Such disparities lead to different solutions to the controversies brought about by the diverse hypotheses of artificial insemination and by the resulting medical responsibility, particularly through the causes of action called wrongful birth and wrongful life. In the legal action known as wrongful life, a person can exercise his or her rights by demanding compensation for damages to his health caused during conception, as part of the right not to be born.